2013
DOI: 10.1175/jcli-d-12-00339.1
|View full text |Cite
|
Sign up to set email alerts
|

Asian Monsoon Forcing of Subtropical Easterlies in the Community Atmosphere Model: Summer Climate Implications for the Western Atlantic

Abstract: The effects of a progressively enhanced Asian summer monsoon on the mean zonal wind are examined in a series of experiments using the Community Atmosphere Model version 4 (CAM4). The response of the barotropic mean zonal wind varies in a linear fashion with the forcings of 5, 10, and 20 W m−2 in net radiation over South Asia. The authors increase the strength of the monsoon by making the South Asian land surface hotter (via lower soil albedo). This leads to an enhanced Rossby wave source region over the Balkan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…only in the zonally asymmetric part of the circulation. Strong zonal overturnings do exist in the northern subtropics during boreal summer, and meridional advection of momentum and vorticity by the upper-tropospheric Asian anticyclone is large even when compared to transports by the zonal-mean flow and transient eddies (e.g., Kelly and Mapes 2013;Shaw 2014). Thus, the overly large strength of the summer cell in our model would not seem to make our results irrelevant to Earth's observed summer circulation.…”
Section: Summary and Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…only in the zonally asymmetric part of the circulation. Strong zonal overturnings do exist in the northern subtropics during boreal summer, and meridional advection of momentum and vorticity by the upper-tropospheric Asian anticyclone is large even when compared to transports by the zonal-mean flow and transient eddies (e.g., Kelly and Mapes 2013;Shaw 2014). Thus, the overly large strength of the summer cell in our model would not seem to make our results irrelevant to Earth's observed summer circulation.…”
Section: Summary and Discussionmentioning
confidence: 77%
“…This change in sign of the absolute vorticity occurred as part of a southward migration of negative relative vorticity from the Northern Hemisphere as the stationary wave amplitude was increased (T. A. Shaw 2015, personal communication) and is distinct from the regime transitions marked by absolute vorticity reaching zero in the region of the off-equatorial heating (e.g., Plumb and Hou 1992;Hsu and Plumb 2000). Nevertheless, the results of Shaw (2014), as well as those of Kelly andMapes (2011, 2013), illustrate the important role played by stationary eddy momentum transports in the boreal summer general circulation. This study is complementary to that work in that we also force an idealized model with a zonally asymmetric thermal forcing, but here we focus on the scaling of the total vertical mass flux, integrated over all longitudes, instead of just the zonal mean.…”
Section: Introductionmentioning
confidence: 97%
“…Dima et al (2005) showed that the structure of the planetary-scale wave transport is consistent with the response of the nonlinear shallow-water equations to a zonally asymmetric off-equatorial heating suggesting that the tropical wave transport is connected to heating in the summer hemisphere. Kelly andMapes (2011, 2013) showed that subtropical stationary wave momentum transport associated with the upper-tropospheric Tibetan anticyclone modulates North American drought through an impact on the North Atlantic subtropical anticyclone. Finally, Shaw and Pauluis (2012) showed that latent heat transport in the vicinity of subtropical anticyclones and monsoons dominates the mass transport by the NH summer circulation in isentropic coordinates.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that regional thermal forcing was associated with global teleconnection patterns; for example, anomalous heating rate in association with the variability of the Indian summer monsoon excited the summertime circumglobal pattern although thermal forcing was regionally prescribed [ Ding and Wang , ; Lin , ]. Kelly and Mapes [] also found that land surface heating over South Asia led to an enhanced Rossby wave source region out of the forcing area. Thus, we will examine the effect of ULSF on the upper tropospheric Rossby wave next.…”
Section: Resultsmentioning
confidence: 99%